The monetary system : its components and some trade issues - Narpati, B. (Rotterdam : Rotterdam University press, 1973)
This book gives a brief survey of the past and present elements of the monetary system and the status of negotiations for reform.
Includes bibliographical references: p. 135-136.
hza 28/01/2019
Loans
Keywords: Special drawing rights; East-West trade; Euro-dollar market; International finance